Role of Smartphones to Support EFL Students English Learning at Border Area - Primus Seran; Aloysia Trivonia Leda Leu; Erlinda Sonya Pale; Fransiska Densiana Luruk (Universitas Nurul Jadid, 2022)
The emergence of the covid-19 outbreak has affected the educational system in Indonesia. The learning process which used to be carried out via face-to-face interaction, needs to be altered to an online way. Because of that, the role of smartphones is very important in learning activities that must be undertaken online. As a place for ongoing learning, the role of smartphones is now widely used to support online learning systems. Hence, this study aims at examining the role of smartphones in the online learning of EFL students at the University of Timor as well as figuring out problems encountered by the subject of the study. In procuring data, the researchers employed a qualitative method. The data was collected from a questionnaire with 21 responses from EFL students from Timor University. Additionally, the researchers also employed interviews and participant observation to enrich the required data. The product of the research indicated that almost all of the students, which was 20 out of 21 (90%) avowed that smartphones gave them benefits especially dealing with their portability. Moreover, the students mentioned running out of credits, dreadful internet connection as well as plenty of distraction coming from social media notifications as existing problems they met while operating smartphones for online learning. Thus, the study results also delineated that smartphones use in online learning during the pandemic was very high and pivotal.